Yield Performance and Phytochemical Stability of ‘Comet’ Hop Under Contrasting Light Supplementation Regimes in Subtropical Conditions - Neves, Caio Scardini [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Campos, Olivia Pak [UNESP]; Viriato, Viviany [UNESP]; do Carmo Fernandes, Gustavo [UNESP]; Cabral, Mariana Nunes Ferreira [UNESP]; Fortuna, Gabriel Cássia [UNESP]; de Oliveira, Sthefani Gonçalves; Rabinowitz, Adam N.; Sarnighausen, Valéria Cristina Rodrigues [UNESP]; Ono, Elizabeth Orika [UNESP]; Silva, Júlio César Rodrigues Lopes; et al. (MDPI, 2025)
This study evaluated the agronomic performance and phytochemical stability of the 'Comet' hop (Humulus lupulus L.) under contrasting photoperiod management regimes (with and without supplemental lighting) in subtropical conditions over two consecutive crop cycles (2024-2025). The experiment, conducted at the School of Agricultural Sciences (FCA/UNESP, Botucatu, Brazil), followed a split-plot factorial design with ten replications. Supplemental lighting (50 W, 6500 K LED floodlights) extended the photoperiod to 17 h during the vegetative stage. Morphometric, phenological, and phytochemical parameters were analyzed, including α- and β-acid contents and essential oil composition by GC-MS and GC-FID. Supplemental lighting significantly increased plant height (590.9 cm), number of lateral branches (70.1), cone length (3.49 cm), and dry cone mass (374.6 g plant-1) while reducing the insertion height of the first cone (99.0 cm). α-Acid content increased from 9.35% to 11.92%, and essential oil content from 1.34% to 1.90%, while β-acid levels showed no significant variation. Chemical analysis identified 31 compounds, predominantly β-myrcene (65-74%) and sesquiterpenes such as (E)-caryophyllene, α-selinene, and β-selinene, exhibiting remarkable compositional stability across years and treatments. Photoperiod extension delayed floral induction, promoted biomass accumulation, and increased cone yield without altering the characteristic herbaceous-resinous aromatic profile. These findings validate supplemental lighting as a decisive strategy to optimize hop production in subtropical regions, ensuring phenological regularity, higher yield, and consistent chemical quality, thereby strengthening the viability of domestic hop cultivation in Brazil.